2013
DOI: 10.1177/1947603513494401
|View full text |Cite
|
Sign up to set email alerts
|

Monounsaturated and Saturated, but Not n-6 Polyunsaturated Fatty Acids Decrease Cartilage Destruction under Inflammatory Conditions

Abstract: Purpose: Osteoarthritis (OA) is associated with obesity in which altered fatty acid levels have been observed. We investigated whether the most common fatty acids in synovial fluid influence cartilage deterioration in OA. Design: Cartilage was obtained from OA patients undergoing total knee arthroplasty. Chondrocytes or cartilage explants were cultured with linoleic (n-6 polyunsaturated), oleic (monounsaturated), or palmitic (saturated) acid. After preculture, media were renewed and inflammation was simulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 36 publications
2
40
1
Order By: Relevance
“…An in vitro study showed that linoleic acid, a fatty acid (FA) had protective effects to the chondrocytes, by decreasing the production of Prostaglandin E2 (PGE2) and nitric oxide (NO) [Shen et al, ]. Bastiaansen‐Jenniskens et al [] showed Linoleic acid had a pro‐inflammatory effect on the cartilage whereas the Palmitic and Oleic acid inhibited the cartilage degradation. In a recent study, increase intakes of MUFA and PUFA were positively associated with decreased joint space width (JSW) loss [Lu et al, ].…”
Section: Dietary Fats and Oamentioning
confidence: 99%
“…An in vitro study showed that linoleic acid, a fatty acid (FA) had protective effects to the chondrocytes, by decreasing the production of Prostaglandin E2 (PGE2) and nitric oxide (NO) [Shen et al, ]. Bastiaansen‐Jenniskens et al [] showed Linoleic acid had a pro‐inflammatory effect on the cartilage whereas the Palmitic and Oleic acid inhibited the cartilage degradation. In a recent study, increase intakes of MUFA and PUFA were positively associated with decreased joint space width (JSW) loss [Lu et al, ].…”
Section: Dietary Fats and Oamentioning
confidence: 99%
“…In vitro, SFAs such as palmitic acid promote the secretion of interleukins (IL) and matrix metalloproteinases (MMP). 4 Other SFAs, such as myristic-and stearic acid induce IL-6 in a dose-dependent way. 2 Nervonic acid, a MUFA with neuroprotective effects as a major component of brain phospholipids, had higher concentrations in the synovial fluid of OA patients than in nonsymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro analysis of the effect of LA (also an n-6 PUFA) on chondrocytes indicate an increase in prostaglandin E2 (PGE2) production in the presence of tumor necrosis factor-α (TNF-α), resulting in increased destruction of chondrocytes. 4 Furthermore, it is described that AA converses to different types of eicosanoids, such as prostaglandins, leukotrienes, and thromboxane mediated by the enzymes cyclooxygenase (COX) and lipoxygenase (LOX). 13 The study of Baker et al 8 demonstrated a correlation between serum AA levels and magnetic resonance imaging signs of synovitis in OA knees, but did not indicate a relation between AA and cartilage loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An in vitro study showed that linoleic acid, a fatty acid (FA) had protective effects to the chondrocytes, by decreasing the production of Prostaglandin E2 (PGE2) and nitric oxide (NO) [129]. Y. M. BastiaansenJenniskens et al showed Linoleic acid had a pro-inflammatory effect on the cartilage whereas the Palmitic and Oleic acid-induced cartilage degradation [130]. In a recent study, increased intakes of MUFA and PUFA were positively associated with decreased joint space width (JSW) loss [131].…”
Section: Role Of Fa In Osteoarthritismentioning
confidence: 99%